Multi-model quantitative MRI of uterine cancers in precision medicine’s era—a narrative review - Marco Gennarini; Rossella Canese; Silvia Capuani; Valentina Miceli; Federica Tomao; Innocenza Palaia; Valentina Zecca; Alessandra Maiuro; Ilaria Balba; Carlo Catalano; Stefania Maria Rita Rizzo; Lucia Manganaro (Insights into Imaging)
Abstract Purpose This review aims to summarize the current applications of quantitative MRI biomarkers in the staging, treatment response evaluation, and prognostication of endometrial (EC) and cervical cancer (CC). By focusing on functional imaging techniques, we explore how these biomarkers enhance personalized cancer management beyond traditional morphological assessments. Methods A structured search of the PubMed database from January to May 2024 was conducted to identify relevant studies on quantitative MRI in uterine cancers. We included studies examining MRI biomarkers like Dynamic Contrast-Enhanced MRI (DCE-MRI), Diffusion-Weighted Imaging (DWI), and Magnetic Resonance Spectroscopy (MRS), emphasizing their roles in assessing tumor physiology, microstructure, and metabolic changes. Results DCE-MRI provides valuable quantitative biomarkers such as Ktrans and Ve, which reflect microvascular characteristics and tumor aggressiveness, outperforming T2-weighted imaging in detecting critical factors like myometrial and cervical invasion. DWI, including advanced models like Intravoxel Incoherent Motion (IVIM), distinguishes between normal and cancerous tissue and correlates with tumor grade and treatment response. MRS identifies metabolic alterations, such as elevated choline and lipid signals, which serve as prognostic markers in uterine cancers. Conclusion Quantitative MRI offers a noninvasive method to assess key biomarkers that inform prognosis and guide treatment decisions in uterine cancers. By providing insights into tumor biology, these imaging techniques represent a significant step forward in the precision medicine era, allowing for a more tailored therapeutic approach based on the unique pathological and molecular characteristics of each tumor. Critical relevance statement Biomarkers obtained from MRI can provide useful quantitative information about the nature of uterine cancers and their prognosis, both at diagnosis and response assessment, allowing better therapeutic strategies to be prepared. Key Points Quantitative MRI improves diagnosis and management of uterine cancers through advanced imaging biomarkers. Quantitative MRI biomarkers enhance staging, prognosis, and treatment response assessment in uterine cancers. Quantitative MRI biomarkers support personalized treatment strategies and improve patient management in uterine cancers. Graphical Abstract